Duplex stainless steel material
By optimizing the chemical composition and metallographic structure of duplex stainless steel, the grain boundary corrosion problem at the welded joints is solved, and excellent grain boundary corrosion resistance is achieved, and the high corrosion resistance requirements of urea manufacturing plants are met.
Patent Information
- Application Number
- CN202380060752.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-08-24
- Filing Date
- 2023-08-23
- Publication Date
- 2025-04-01
AI Technical Summary
In urea manufacturing plants, duplex stainless steel is prone to grain boundary corrosion at welded joints, resulting in a decrease in corrosion resistance.
By optimizing the chemical composition and metallographic structure of duplex stainless steel, it ensures its excellent grain boundary corrosion resistance at the welded joints. Specific measures include controlling element content in chemical composition and controlling the mean thickness and standard deviation of ferrite and austenite in metallographic structure.
It realizes excellent grain boundary corrosion resistance of duplex stainless steel at welded joints, reduces corrosion speed, and meets the high corrosion resistance requirements of urea manufacturing plants.
Smart Images

Figure CN119744312A_ABST
Abstract
Description
Technical Field
[0001] The present disclosure relates to a duplex stainless steel material. Background Art
[0002] Urea is produced in a urea plant, which is one of the chemical plants. Urea is produced in the following way in a urea plant. Urea is heated to 120 kg / cm2 at a high temperature of 160 to 230 °C. 2 The above high pressure synthesis produces a mixed gas containing ammonia and carbon dioxide. At this time, urea is produced by the synthesis reaction.
[0003] In the above-mentioned urea production process, an intermediate substance called ammonium carbamate is generated. Ammonium carbamate is very corrosive and promotes intergranular corrosion of steel. Therefore, excellent intergranular corrosion resistance is required in steel used in urea plants.
[0004] Duplex stainless steel has excellent corrosion resistance. Therefore, duplex stainless steel is used as a steel material for urea production plants. Duplex stainless steel for urea production plants is proposed, for example, in Japanese Patent Application Publication No. 2003-301241 (Patent Document 1) and Japanese Patent Application Publication No. 2011-127186 (Patent Document 2).
[0005] The duplex stainless steel material disclosed in Patent Document 1 attempts to improve corrosion resistance from the perspective of chemical composition. Specifically, the content of Cu that accelerates the corrosion rate is suppressed. In addition, the content of Mo that promotes the formation of the σ phase is suppressed, and W is contained. This W is a ferrite stabilizing element that replaces Mo and does not promote the formation of the σ phase. Therefore, Patent Document 1 records that the corrosion resistance of the duplex stainless steel material is improved.
[0006] The duplex stainless steel material disclosed in Patent Document 2 attempts to improve corrosion resistance from the perspective of chemical composition. Specifically, by defining a relationship between Nd content, P content, S content, Al content, and Mo content so that the relationship is within a predetermined range, the formation of σ phase at the interface between ferrite and austenite is suppressed. As a result, Patent Document 2 describes that the corrosion resistance of the duplex stainless steel material is improved.
[0007] Prior art literature
[0008] Patent Literature
[0009] Patent Document 1: Japanese Patent Application Publication No. 2003-301241
[0010] Patent Document 2: Japanese Patent Application Publication No. 2011-127186
[0011] However, duplex stainless steel materials used in urea manufacturing plants may be welded during factory construction to form welded joints. In such welded joints, a heat-affected zone (HAZ) is formed in the base material portion adjacent to the weld metal. In welded joints, intergranular corrosion is prone to develop in the HAZ. Therefore, even when duplex stainless steel materials are used as welded joints, excellent intergranular corrosion resistance is required. Summary of the invention
[0012] Problem that the invention aims to solve
[0013] An object of the present disclosure is to provide a duplex stainless steel material having excellent intergranular corrosion resistance even when used as a welded joint.
[0014] Solutions for solving problems
[0015] The chemical composition of the duplex stainless steel material disclosed in the present invention is expressed in mass %.
[0016] C: 0.030% or less,
[0017] Si: 0.50% or less,
[0018] Mn: 2.00% or less,
[0019] P: 0.040% or less,
[0020] S: 0.0010% or less,
[0021] Cr: 26.0~28.0%,
[0022] Ni: 6.0-10.0%,
[0023] Mo: 0.20~1.70%,
[0024] W: more than 2.00% and less than 3.00%,
[0025] N: more than 0.30% and less than 0.40%,
[0026] O: 0.020% or less,
[0027] Al: 0.050% or less,
[0028] Cu: 0-0.30%,
[0029] Co: 0-1.0%,
[0030] Ti: 0~0.300%,
[0031] Nb: 0~0.300%,
[0032] Ca: 0~0.010%
[0033] Mg: 0~0.010%,
[0034] B: 0 to 0.010%, and
[0035] The balance is Fe and impurities.
[0036] The length direction of the duplex stainless steel is defined as the L direction, and the thickness direction of the duplex stainless steel is defined as the T direction.
[0037] In the cross section of the duplex stainless steel material including the L direction and the T direction, three rectangular regions were determined at 100 mm intervals in the L direction, and each of the determined regions was set as a rectangle of 200 μm in the L direction and 200 μm in the T direction.
[0038] In each rectangular area,
[0039] When the five line segments are defined as the line segments LS, the five line segments are line segments extending in the T direction and are arranged at equal intervals in the L direction of the rectangular area, dividing the rectangular area into six equal parts in the L direction.
[0040] The average thickness TF of each ferrite in the three rectangular regions overlapping the 15 line segments LS is 2.50 to 4.50 μm, and the sample standard deviation ΔTF of the ferrite thickness is less than 0.50 μm.
[0041] The average thickness TA of each austenite overlapping the 15 line segments LS is 2.50 to 4.50 μm.
[0042] Effects of the Invention
[0043] The duplex stainless steel material disclosed herein has excellent intergranular corrosion resistance even when used as a welded joint. BRIEF DESCRIPTION OF THE DRAWINGS
[0044] Figure 1 This is a schematic diagram of a longitudinal cross section of a duplex stainless steel material including the length direction (L direction) and the thickness direction (T direction).
[0045] Figure 2 This is a schematic diagram of a longitudinal cross section of a duplex stainless steel material in the case where the duplex stainless steel material is welded to form a welded joint.
[0046] Figure 3 This is a longitudinal cross-sectional view of a duplex stainless steel material for explaining a method of determining a rectangular region TP for measuring an average thickness TF of ferrite, a sample standard deviation ΔTF of the thickness of ferrite, and an average thickness TA of austenite of the duplex stainless steel material when the duplex stainless steel material is a steel pipe.
[0047] Figure 4 yes Figure 3 Schematic diagram of the rectangular area TP in .
[0048] Figure 5 yes Figure 4 An enlarged view of the area in the rectangular area in , which overlaps with the line segment LS1. DETAILED DESCRIPTION
[0049] The present inventors have studied duplex stainless steel materials having excellent intergranular corrosion resistance even in the case of welded joints. As a result, the present inventors have obtained the following findings.
[0050] First, the present inventors studied a duplex stainless steel material having excellent intergranular corrosion resistance even when used as a welded joint from the viewpoint of chemical composition, similar to Patent Documents 1 and 2. As a result, the present inventors believed that if the chemical composition of the duplex stainless steel material satisfies the following feature 1, excellent intergranular corrosion resistance can be obtained even when used as a welded joint.
[0051] (Feature 1)
[0052] The chemical composition contains, by mass%, C: less than 0.030%, Si: less than 0.50%, Mn: less than 2.00%, P: less than 0.040%, S: less than 0.0010%, Cr: 26.0-28.0%, Ni: 6.0-10.0%, Mo: 0.20-1.70%, W: greater than 2.00% and less than 3.00%, N: greater than 0.30% and less than 0.40%, O: less than 0.020%, Al: less than 0.050%, Cu: 0-0.30%, Co: 0-1.0%, Ti: 0-0.300%, Nb: 0-0.300%, Ca: 0-0.010%, Mg: 0-0.010%, B: 0-0.010%, and the balance, which is Fe and impurities.
[0053] Therefore, the present inventors have further studied the following scheme: even when duplex stainless steel is welded to form a welded joint, sufficient intergranular corrosion resistance can be obtained. When duplex stainless steel is welded to form a welded joint, as described above, intergranular corrosion is prone to occur particularly in the heat-affected zone (HAZ). Therefore, the metallographic structure at the HAZ and the metallographic structure at the base material part other than the HAZ when the duplex stainless steel is used as a welded joint were observed. As a result, the present inventors have obtained the following insights.
[0054] The metallographic structure of duplex stainless steel is substantially composed of ferrite and austenite. Specifically, in a cross section (hereinafter also referred to as a longitudinal cross section) including the length direction (L direction) and the thickness direction (T direction) of the duplex stainless steel, as shown in FIG. Figure 1 As shown in this way, ferrite F and austenite A are stacked in layers.
[0055] When duplex stainless steel is welded to form a welded joint, the metallographic structure of the HAZ is also composed of ferrite and austenite. When the metallographic structure of the HAZ where intergranular corrosion occurs is compared with the metallographic structure of the HAZ where intergranular corrosion is not observed, ferrite and austenite of the same size are observed in both the metallographic structure of the HAZ where intergranular corrosion occurs and the metallographic structure of the HAZ where intergranular corrosion is not observed. However, if Figure 2 As shown, in the metallographic structure of the HAZ where intergranular corrosion occurred, many Cr nitrides and secondary austenite MA were also generated in the ferrite F. Secondary austenite refers to austenite that is significantly finer than the above-mentioned austenite A. The results of the investigation revealed that such Cr nitrides and secondary austenite MA are generated during welding.
[0056] Based on the above findings, the present inventors believed that the main reason for the reduction in intergranular corrosion resistance of the HAZ of the welded joint of the duplex stainless steel material is the Cr nitride and secondary austenite generated during welding. Therefore, the present inventors studied a method for suppressing the amount of Cr nitride and secondary austenite generated during welding. As a result, the present inventors obtained the following findings.
[0057] As described above, Cr nitride and secondary austenite are generated from ferrite during welding. Therefore, in the ferrite and austenite stacked in layers, if the thickness of ferrite (that is, the length in the T direction) increases, the distance that N dissolved in ferrite during welding diffuses into austenite during the cooling process becomes longer. Moreover, during the welding process, the cooling time is short, so the time available for diffusion is short. Therefore, it is believed that Cr nitride is easy to generate and secondary austenite is easy to generate during welding.
[0058] Furthermore, it is considered that if there is a fluctuation in the thickness of ferrite in the L direction in the longitudinal section of the duplex stainless steel material, Cr nitrides and secondary austenite are likely to be generated during welding in the wider portion (thicker portion) of the ferrite extending along the L direction.
[0059] As described above, the present inventors have considered that narrowing the width (thickness) of ferrite and reducing the variation in the width (thickness) of ferrite are effective in order to suppress the amount of Cr nitride and secondary austenite generated during welding.
[0060] Therefore, the metallographic structure of duplex stainless steel was further studied. As a result, it was found that if the metallographic structure of duplex stainless steel satisfies the following characteristics, the intergranular corrosion resistance of the HAZ in the case of a welded joint will be significantly improved.
[0061] (Feature 2)
[0062] The length direction of the duplex stainless steel material is defined as the L direction, and the thickness direction of the duplex stainless steel material is defined as the T direction. In the cross section of the duplex stainless steel material including the L direction and the T direction, three rectangular areas are determined at intervals of 100 mm in the L direction. Each determined area is set as a rectangle of 200 μm in the L direction and 200 μm in the T direction. In each rectangular area, five line segments are defined as line segments LS, which are line segments extending in the T direction and are arranged at equal intervals in the L direction of the rectangular area, dividing the rectangular area into six equal parts in the L direction. In this case, the following (1) to (3) are satisfied.
[0063] (1) The average thickness TF of each ferrite in the three rectangular regions overlapping the 15 line segments LS is 2.50 to 4.50 μm.
[0064] (2) The sample standard deviation ΔTF of the thickness of ferrite is 0.50 μm or less.
[0065] (3) The average thickness TA of each austenite overlapping the 15 line segments LS is 2.50 to 4.50 μm.
[0066] The duplex stainless steel material of the present embodiment completed based on the above findings has the following configuration.
[0067] [1] The chemical composition of the duplex stainless steel material of the first constitution is expressed in mass % as follows:
[0068] C: 0.030% or less,
[0069] Si: 0.50% or less,
[0070] Mn: 2.00% or less,
[0071] P: 0.040% or less,
[0072] S: 0.0010% or less,
[0073] Cr: 26.0~28.0%,
[0074] Ni: 6.0-10.0%,
[0075] Mo: 0.20~1.70%,
[0076] W: more than 2.00% and less than 3.00%,
[0077] N: more than 0.30% and less than 0.40%,
[0078] O: 0.020% or less,
[0079] Al: 0.050% or less,
[0080] Cu: 0-0.30%,
[0081] Co: 0-1.0%,
[0082] Ti: 0~0.300%,
[0083] Nb: 0~0.300%,
[0084] Ca: 0~0.010%
[0085] Mg: 0~0.010%,
[0086] B: 0 to 0.010%, and
[0087] The balance is Fe and impurities.
[0088] The length direction of the duplex stainless steel is defined as the L direction, and the thickness direction of the duplex stainless steel is defined as the T direction.
[0089] In the cross section of the duplex stainless steel material including the L direction and the T direction, three rectangular regions were determined at 100 mm intervals in the L direction, and each of the determined regions was set as a rectangle of 200 μm in the L direction and 200 μm in the T direction.
[0090] In each rectangular area,
[0091] When the five line segments are defined as the line segments LS, the five line segments are line segments extending in the T direction and are arranged at equal intervals in the L direction of the rectangular area, dividing the rectangular area into six equal parts in the L direction.
[0092] The average thickness TF of each ferrite in the three rectangular regions overlapping the 15 line segments LS is 2.50 to 4.50 μm, and the sample standard deviation ΔTF of the ferrite thickness is less than 0.50 μm.
[0093] The average thickness TA of each austenite overlapping the 15 line segments LS is 2.50 to 4.50 μm.
[0094] [2] A duplex stainless steel material according to a second configuration is the duplex stainless steel material according to the first configuration, wherein:
[0095] The chemical composition contains
[0096] Cu: 0.01-0.30%,
[0097] Co: 0.1-1.0%,
[0098] Ti: 0.001~0.300%,
[0099] Nb: 0.001~0.300%,
[0100] Ca: 0.001~0.010%,
[0101] Mg: 0.001-0.010%, and
[0102] B: One or more elements selected from the group consisting of 0.001 to 0.010%.
[0103] [3] A duplex stainless steel material according to a third configuration is a duplex stainless steel material according to the first or second configuration, wherein:
[0104] Duplex stainless steel is a seamless steel pipe.
[0105] The duplex stainless steel material of the present embodiment will be described in detail below. Unless otherwise specified, "%" related to an element means mass %.
[0106] [Characteristics of the duplex stainless steel material of this embodiment]
[0107] The duplex stainless steel material of the present embodiment satisfies the following features 1 and 2.
[0108] (Feature 1)
[0109] The chemical composition contains, by mass%, C: less than 0.030%, Si: less than 0.50%, Mn: less than 2.00%, P: less than 0.040%, S: less than 0.0010%, Cr: 26.0-28.0%, Ni: 6.0-10.0%, Mo: 0.20-1.70%, W: greater than 2.00% and less than 3.00%, N: greater than 0.30% and less than 0.40%, O: less than 0.020%, Al: less than 0.050%, Cu: 0-0.30%, Co: 0-1.0%, Ti: 0-0.300%, Nb: 0-0.300%, Ca: 0-0.010%, Mg: 0-0.010%, B: 0-0.010%, and the balance, which is Fe and impurities.
[0110] (Feature 2)
[0111] The length direction of the duplex stainless steel material is defined as the L direction, and the thickness direction of the duplex stainless steel material is defined as the T direction. In the cross section of the duplex stainless steel material including the L direction and the T direction, three rectangular areas are determined at intervals of 100 mm in the L direction. Each determined area is set as a rectangle of 200 μm in the L direction and 200 μm in the T direction. In each rectangular area, five line segments are defined as line segments LS, which are line segments extending in the T direction and are arranged at equal intervals in the L direction of the rectangular area, dividing the rectangular area into six equal parts in the L direction. In this case, the following (1) to (3) are satisfied.
[0112] (1) The average thickness TF of each ferrite in the three rectangular regions overlapping the 15 line segments LS is 2.50 to 4.50 μm.
[0113] (2) The sample standard deviation ΔTF of the thickness of ferrite is 0.50 μm or less.
[0114] (3) The average thickness TA of each austenite overlapping the 15 line segments LS is 2.50 to 4.50 μm.
[0115] Hereinafter, feature 1 and feature 2 will be described.
[0116] [For (Feature 1) Chemical composition]
[0117] The chemical composition of the duplex stainless steel material according to the present embodiment contains the following elements.
[0118] C: 0.030% or less
[0119] Carbon (C) is inevitably contained. That is, the C content is greater than 0%. C forms carbides and increases the strength of the steel. However, if the C content is greater than 0.030%, Cr carbides are formed at the grain boundaries. In this case, even if the contents of other elements are within the range of this embodiment, the intergranular corrosion resistance of the steel is reduced.
[0120] Therefore, the C content is 0.030% or less.
[0121] The C content is preferably as low as possible. However, excessive reduction in the C content significantly increases the manufacturing cost. Therefore, in consideration of industrial production, the preferred lower limit of the C content is 0.001%, more preferably 0.002%, and further preferably 0.005%.
[0122] The upper limit of the C content is preferably 0.028%, more preferably 0.025%, further preferably 0.022%, further preferably 0.020%.
[0123] Si: 0.50% or less
[0124] Silicon (Si) is inevitably contained. That is, the Si content is greater than 0%. Si deoxidizes the steel in the steelmaking stage of the steel production process.
[0125] On the other hand, when the Si content exceeds 0.50%, Si segregates to the grain boundaries. In this case, even if the contents of other elements are within the ranges of the present embodiment, the intergranular corrosion resistance of the steel material decreases.
[0126] Therefore, the Si content is 0.50% or less.
[0127] The lower limit of the Si content is preferably 0.01%, more preferably 0.02%, and further preferably 0.05%.
[0128] The upper limit of the Si content is preferably 0.45%, more preferably 0.40%, further preferably 0.38%, further preferably 0.35%.
[0129] Mn: 2.00% or less
[0130] Manganese (Mn) is inevitably contained. That is, the Mn content is greater than 0%. Mn deoxidizes the steel in the steelmaking stage of the steel manufacturing process. Mn is also an austenite forming element, which stabilizes the austenite in the steel. As for the Mn content, as long as Mn is contained, even if it is contained in a small amount, the above effect can be obtained to a certain extent.
[0131] However, if the Mn content exceeds 2.00%, Mn segregates to the grain boundaries together with impurities such as P and S. In this case, even if the contents of other elements are within the ranges of the present embodiment, the corrosion resistance of the steel material in a high temperature environment decreases.
[0132] Therefore, the Mn content is 2.00% or less.
[0133] The lower limit of the Mn content is preferably 0.01%, more preferably 0.05%, and further preferably 0.10%.
[0134] The upper limit of the Mn content is preferably 1.60%, more preferably 1.40%, more preferably 1.20%, more preferably 1.00%, more preferably 0.90%, more preferably 0.80%, and more preferably 0.70%.
[0135] P: 0.040% or less
[0136] Phosphorus (P) is an impurity, and the P content is greater than 0%. If the P content is greater than 0.040%, P segregates to the grain boundaries even if the contents of other elements are within the ranges of the present embodiment. Therefore, the intergranular corrosion resistance of the steel material decreases.
[0137] Therefore, the P content is 0.040% or less.
[0138] The P content is preferably as low as possible. However, excessive reduction of the P content significantly increases the manufacturing cost. Therefore, in consideration of industrial production, the preferred lower limit of the P content is 0.001%, more preferably 0.002%, and further preferably 0.005%.
[0139] The upper limit of the P content is preferably 0.035%, more preferably 0.030%, further preferably 0.025%, further preferably 0.020%, further preferably 0.015%.
[0140] S: 0.0010% or less
[0141] Sulfur (S) is an impurity, and the S content is greater than 0%. If the S content is greater than 0.0010%, S segregates to the grain boundaries even if the contents of other elements are within the ranges of the present embodiment. Therefore, the intergranular corrosion resistance of the steel material decreases.
[0142] Therefore, the S content is 0.0010% or less.
[0143] The S content is preferably as low as possible. However, excessive reduction of the S content significantly increases the manufacturing cost. Therefore, in consideration of industrial production, the preferred lower limit of the S content is 0.0001%, and more preferably 0.0002%.
[0144] The upper limit of the S content is preferably 0.0009%, more preferably 0.0007%, and further preferably 0.0005%.
[0145] Cr: 26.0~28.0%
[0146] Chromium (Cr) forms a solid solution and improves the intergranular corrosion resistance of steel. Cr also stabilizes the ferrite in the steel and improves the intergranular corrosion resistance of the steel. If the Cr content is less than 26.0%, the above effects cannot be fully obtained even if the contents of other elements are within the range of the present embodiment.
[0147] On the other hand, if the Cr content exceeds 28.0%, a σ (sigma) phase is generated in the steel material even if the contents of other elements are within the ranges of the present embodiment. The σ phase reduces the intergranular corrosion resistance of the steel material.
[0148] Therefore, the Cr content is 26.0 to 28.0%.
[0149] The lower limit of the Cr content is preferably 26.1%, more preferably 26.2%, further preferably 26.3%, further preferably 26.4%.
[0150] The upper limit of the Cr content is preferably 27.9%, more preferably 27.8%, further preferably 27.7%, further preferably 27.6%.
[0151] Ni: 6.0~10.0%
[0152] Nickel (Ni) stabilizes austenite in steel. That is, Ni stabilizes the dual-phase structure of ferrite and austenite. Therefore, the intergranular corrosion resistance of the steel is improved. If the Ni content is less than 6.0%, even if the content of other elements is within the range of this embodiment, the above-mentioned effect cannot be fully obtained.
[0153] On the other hand, if the Ni content exceeds 10.0%, the ratio of austenite in the steel material becomes excessively high even if the contents of other elements are within the ranges of the present embodiment. In this case, the intergranular corrosion resistance of the steel material decreases.
[0154] Therefore, the Ni content is 6.0 to 10.0%.
[0155] The lower limit of the Ni content is preferably 6.2%, more preferably 6.3%, further preferably 6.4%, further preferably 6.5%.
[0156] The upper limit of the Ni content is preferably 9.5%, more preferably 9.0%, further preferably 8.5%, further preferably 8.0%.
[0157] Mo: 0.20~1.70%
[0158] Molybdenum (Mo) improves the intergranular corrosion resistance of steel materials. If the Mo content is less than 0.20%, the above-mentioned effects cannot be fully obtained even if the contents of other elements are within the ranges of the present embodiment.
[0159] On the other hand, if the Mo content exceeds 1.70%, even if the contents of other elements are within the ranges of the present embodiment, a σ phase is generated. In this case, the intergranular corrosion resistance of the steel material decreases.
[0160] Therefore, the Mo content is 0.20 to 1.70%.
[0161] The lower limit of the Mo content is preferably 0.30%, more preferably 0.40%, and further preferably 0.50%.
[0162] The upper limit of the Mo content is preferably 1.60%, more preferably 1.50%, more preferably 1.40%, more preferably 1.30%, more preferably 1.20%, more preferably 1.10%, and more preferably 1.00%.
[0163] W: more than 2.00% and less than 3.00%
[0164] Tungsten (W) improves the intergranular corrosion resistance of steel materials. If the W content is 2.00% or less, the above-mentioned effects cannot be fully obtained even if the contents of other elements are within the ranges of the present embodiment.
[0165] On the other hand, if the W content exceeds 3.00%, even if the contents of other elements are within the ranges of the present embodiment, the σ phase is generated. In this case, the intergranular corrosion resistance of the steel material decreases.
[0166] Therefore, the W content is more than 2.00% and less than or equal to 3.00%.
[0167] The lower limit of the W content is preferably 2.01%, more preferably 2.02%, more preferably 2.05%, more preferably 2.08%, more preferably 2.10%, and still more preferably 2.12%.
[0168] The upper limit of the W content is preferably 2.90%, more preferably 2.80%, more preferably 2.70%, more preferably 2.60%, more preferably 2.50%, more preferably 2.40%, and more preferably 2.30%.
[0169] N: more than 0.30% and less than 0.40%
[0170] Nitrogen (N) stabilizes austenite in steel. That is, N stabilizes the dual-phase structure of ferrite and austenite. Therefore, the intergranular corrosion resistance of the steel is improved. If the N content is less than 0.30%, even if the content of other elements is within the range of this embodiment, the above-mentioned effect cannot be fully obtained.
[0171] On the other hand, when the N content exceeds 0.40%, the hot workability of the steel material decreases even if the contents of other elements are within the ranges of the present embodiment.
[0172] Therefore, the N content is greater than 0.30% and less than or equal to 0.40%.
[0173] The lower limit of the N content is preferably 0.31%, more preferably 0.32%.
[0174] The upper limit of the N content is preferably 0.39%, more preferably 0.38%, and further preferably 0.37%.
[0175] O: 0.020% or less
[0176] Oxygen (O) is an impurity, and the O content is greater than 0%. If the O content is greater than 0.020%, excessive oxides are generated in the steel. In this case, even if the contents of other elements are within the range of this embodiment, the intergranular corrosion resistance of the steel is reduced.
[0177] Therefore, the O content is 0.020% or less.
[0178] The O content is preferably as low as possible. However, excessive reduction of the O content significantly increases the manufacturing cost. Therefore, in consideration of industrial productivity, the preferred lower limit of the O content is 0.001%, more preferably 0.002%, and further preferably 0.005%.
[0179] The upper limit of the O content is preferably 0.018%, more preferably 0.016%, and further preferably 0.014%.
[0180] Al: 0.050% or less
[0181] Aluminum (Al) is inevitably contained. That is, the Al content is greater than 0%. Al deoxidizes the steel. However, if the Al content is greater than 0.050%, excessive oxides are generated in the steel. In this case, even if the content of other elements is within the range of this embodiment, the intergranular corrosion resistance of the steel is reduced.
[0182] Therefore, the Al content is 0.050% or less.
[0183] The lower limit of the Al content is preferably 0.001%, more preferably 0.003%, and further preferably 0.005%.
[0184] The upper limit of the Al content is preferably 0.045%, more preferably 0.040%, further preferably 0.038%, further preferably 0.036%.
[0185] In the chemical composition of the duplex stainless steel material of the present embodiment, the Al content means "acid-soluble Al", that is, the content of sol.Al.
[0186] The balance of the chemical composition of the duplex stainless steel material of the present embodiment is Fe and impurities. The impurities in the chemical composition are elements that are mixed from ores, scraps, or the manufacturing environment as raw materials when the duplex stainless steel material is industrially manufactured, and are not intentionally contained elements. They are allowable elements within a range that does not adversely affect the duplex stainless steel material of the present embodiment.
[0187] [Optional Elements]
[0188] The chemical composition of the duplex stainless steel material of the present embodiment may further contain
[0189] Cu: 0-0.30%,
[0190] Co: 0-1.0%,
[0191] Ti: 0~0.300%,
[0192] Nb: 0~0.300%,
[0193] Ca: 0~0.010%
[0194] Mg: 0-0.010%, and
[0195] B: one or more elements selected from the group consisting of 0 to 0.010%.
[0196] These optional elements are described below.
[0197] [For Group 1: Cu and Co]
[0198] The chemical composition of the duplex stainless steel material of the present embodiment may further contain one or more elements selected from the group consisting of Cu and Co to replace a portion of Fe. These elements are all arbitrary elements and may not be contained. When contained, Cu and Co improve the intergranular corrosion resistance of the steel material.
[0199] Cu: 0~0.30%
[0200] Copper (Cu) is an arbitrary element and may not be contained. In other words, the Cu content may be 0%.
[0201] When Cu is contained, that is, when the Cu content is greater than 0%, Cu strengthens the passive film and improves the corrosion resistance of the duplex stainless steel. Cu also stabilizes austenite. As long as Cu is contained, even if the content is small, the above effect can be obtained to a certain extent.
[0202] However, if the Cu content exceeds 0.30%, even if the contents of other elements are within the ranges of the present embodiment, corrosion of the duplex stainless steel material is promoted under the corrosive environment of a urea production plant.
[0203] Therefore, the Cu content is 0 to 0.30%.
[0204] The lower limit of the Cu content is preferably 0.01%, more preferably 0.05%.
[0205] The upper limit of the Cu content is preferably 0.29%, more preferably 0.27%, further preferably 0.25%, further preferably 0.22%.
[0206] Co: 0~1.0%
[0207] Cobalt (Co) is an arbitrary element and may not be contained. In other words, the Co content may be 0%.
[0208] When Co is contained, that is, when the Co content is greater than 0%, Co strengthens the passive film and improves the corrosion resistance of the duplex stainless steel. Co also stabilizes austenite. As long as Co is contained, even if the content is small, the above effect can be obtained to a certain extent.
[0209] However, if the Co content exceeds 1.0%, the manufacturing cost increases extremely even if the contents of other elements are within the ranges of the present embodiment.
[0210] Therefore, the Co content is 0 to 1.0%.
[0211] The preferred lower limit of the Co content is 0.1%, more preferably 0.2%, and further preferably 0.3%. The preferred upper limit of the Co content is 0.9%, further preferably 0.8%, and further preferably 0.7%.
[0212] [For Group 2: Ti and Nb]
[0213] Alternatively, the chemical composition of the duplex stainless steel material of the present embodiment may further contain one or more elements selected from the group consisting of Ti and Nb to replace a portion of Fe. These elements are all arbitrary elements and may not be contained. When contained, Ti and Nb increase the strength of the steel material.
[0214] Ti: 0~0.300%
[0215] Titanium (Ti) is an arbitrary element and may not be contained. In other words, the Ti content may be 0%.
[0216] When Ti is contained, that is, when the Ti content is greater than 0%, Ti forms carbonitrides and improves the strength of the steel. Ti also suppresses the formation of Cr carbonitrides by forming carbonitrides. Therefore, the intergranular corrosion resistance of the steel is improved. As long as Ti is contained, even if it is contained in a small amount, the above effect can be obtained to a certain extent.
[0217] However, if the Ti content exceeds 0.300%, even if the contents of other elements are within the ranges of the present embodiment, the strength of the steel material becomes too high and the toughness of the steel material decreases.
[0218] Therefore, the Ti content is 0 to 0.300%.
[0219] The lower limit of the Ti content is preferably 0.001%, more preferably 0.005%, further preferably 0.010%, further preferably 0.015%, further preferably 0.020%.
[0220] The upper limit of the Ti content is preferably 0.250%, more preferably 0.200%, more preferably 0.150%, more preferably 0.100%, more preferably 0.090%, more preferably 0.080%, and more preferably 0.070%.
[0221] Nb: 0~0.300%
[0222] Niobium (Nb) is an arbitrary element and may not be contained. In other words, the Nb content may be 0%.
[0223] When Nb is contained, that is, when the Nb content is greater than 0%, Nb forms carbonitrides and improves the strength of the steel. Nb also suppresses the formation of Cr carbonitrides by forming carbonitrides. Therefore, the intergranular corrosion resistance of the steel is improved. As long as Nb is contained, even if it is contained in a small amount, the above effect can be obtained to a certain extent.
[0224] However, if the Nb content exceeds 0.300%, even if the contents of other elements are within the ranges of the present embodiment, the strength of the steel material becomes too high and the toughness of the steel material decreases.
[0225] Therefore, the Nb content is 0 to 0.300%.
[0226] The lower limit of the Nb content is preferably 0.001%, more preferably 0.005%, further preferably 0.010%, further preferably 0.015%, further preferably 0.020%.
[0227] The upper limit of the Nb content is preferably 0.250%, more preferably 0.200%, further preferably 0.150%, further preferably 0.120%, further preferably 0.110%, further preferably 0.100%.
[0228] [For Group 3: Ca, Mg and B]
[0229] The chemical composition of the duplex stainless steel material of the present embodiment may further contain one or more elements selected from the group consisting of Ca, Mg and B to replace a portion of Fe. These elements are all arbitrary elements and may not be contained. When contained, Ca, Mg and B improve the hot workability of the steel material.
[0230] Ca: 0~0.010%
[0231] Calcium (Ca) is an arbitrary element and may not be contained. In other words, the Ca content may be 0%.
[0232] When Ca is contained, that is, when the Ca content is greater than 0%, Ca fixes S in the steel material as sulfides to render it harmless, thereby improving the hot workability of the steel material. As long as Ca is contained, even if the content is small, the above effect can be obtained to a certain extent.
[0233] However, if the Ca content exceeds 0.010%, even if the contents of other elements are within the ranges of the present embodiment, oxides in the steel material will coarsen and the toughness of the steel material will decrease.
[0234] Therefore, the Ca content is 0 to 0.010%.
[0235] The lower limit of the Ca content is preferably 0.001%, more preferably 0.002%.
[0236] The upper limit of the Ca content is preferably 0.009%, more preferably 0.008%, further preferably 0.007%, further preferably 0.006%, further preferably 0.005%.
[0237] Mg: 0~0.010%
[0238] Magnesium (Mg) is an arbitrary element and may not be contained. In other words, the Mg content may be 0%.
[0239] When Mg is contained, that is, when the Mg content is greater than 0%, Mg fixes S in the steel material as sulfide to render it harmless, thereby improving the hot workability of the steel material. As long as Mg is contained, even if the content is small, the above effect can be obtained to a certain extent.
[0240] However, if the Mg content exceeds 0.010%, even if the contents of other elements are within the ranges of the present embodiment, oxides in the steel material will coarsen and the toughness of the steel material will decrease.
[0241] Therefore, the Mg content is 0 to 0.010%.
[0242] The lower limit of the Mg content is preferably 0.001%, more preferably 0.002%.
[0243] The upper limit of the Mg content is preferably 0.009%, more preferably 0.008%, more preferably 0.007%, more preferably 0.006%, and still more preferably 0.005%.
[0244] B: 0~0.010%
[0245] Boron (B) is an arbitrary element and may not be contained. In other words, the B content may be 0%.
[0246] When B is contained, that is, when the B content is greater than 0%, B suppresses the segregation of S in the steel material to the grain boundaries and improves the hot workability of the steel material. As long as B is contained, even if the content is small, the above effect can be obtained to a certain extent.
[0247] However, if the B content exceeds 0.010%, even if the contents of other elements are within the ranges of the present embodiment, boron nitride (BN) is generated and the toughness of the steel material decreases.
[0248] Therefore, the B content is 0 to 0.010%.
[0249] The lower limit of the B content is preferably 0.001%, more preferably 0.002%.
[0250] The upper limit of the B content is preferably 0.009%, more preferably 0.008%, more preferably 0.007%, more preferably 0.006%, more preferably 0.005%, and still more preferably 0.004%.
[0251] [Metallurgical structure]
[0252] The metallographic structure of the duplex stainless steel material of the present embodiment is composed of ferrite and austenite. In this specification, "composed of ferrite and austenite" means that the phases other than ferrite and austenite are so few that they can be ignored. The metallographic structure of the duplex stainless steel material of the present embodiment may also contain a small amount of precipitates, inclusions, etc. in addition to ferrite and austenite. The area ratio of precipitates and inclusions in the metallographic structure of the duplex stainless steel material of the present embodiment is low to a negligible degree compared with the area ratio of ferrite and austenite.
[0253] In the metallographic structure of the duplex stainless steel material of the present embodiment, the area ratio of ferrite is 35 to 55%. The preferred lower limit of the area ratio of ferrite is 37%, more preferably 39%. The preferred upper limit of the area ratio of ferrite is 53%, more preferably 51%.
[0254] [Method for measuring ferrite area ratio]
[0255] In the present embodiment, the area ratio of ferrite in the duplex stainless steel material can be obtained by the following method.
[0256] The length direction of the duplex stainless steel material of the present embodiment is defined as the L direction, and the thickness direction is defined as the T direction. Specifically, when the duplex stainless steel material is a steel pipe, the pipe axis direction (rolling direction) is the L direction, and the wall thickness direction is the T direction. When the duplex stainless steel material is a steel plate, the length direction (rolling direction) is the L direction, and the plate thickness direction is the T direction. When the duplex stainless steel material is a steel bar, the center axis direction (length direction) is the L direction, and the radial direction is the T direction.
[0257] A test piece is collected from the middle of the thickness of the duplex stainless steel material, and the test piece includes a longitudinal section including the L direction and the T direction on the surface. When the duplex stainless steel material is a steel pipe, the test piece is collected from the middle of the wall thickness. When the duplex stainless steel material is a steel plate, the test piece is collected from the center of the plate thickness. When the duplex stainless steel material is a steel bar, the test piece is collected from the center of the cross section perpendicular to the L direction.
[0258] The surface of the test piece corresponding to the longitudinal section (the surface including the L direction and the T direction) is defined as the observation surface. The size of the test piece is not particularly limited, and an observation surface of 5 mm in the L direction x 5 mm in the T direction may be obtained.
[0259] The observation surface of the test piece was mirror-polished. The mirror-polished observation surface was electrolytically etched in a 30% sodium hydroxide etching solution to visualize the structure. The observation surface with the structure visualized was observed with 10 fields of view using an optical microscope. The area of the observation field is not particularly limited, and is, for example, 4.00×10 4 μm 2 (Magnification 500 times).
[0260] In each field of view, ferrite and austenite are determined from the contrast. The area ratios of the determined ferrite and austenite are calculated. The method for calculating the area ratios of the determined ferrite and austenite is not particularly limited, and any well-known method may be used. For example, the area ratios of ferrite and austenite can be calculated using image analysis. In the present embodiment, the arithmetic mean of the area ratios of ferrite calculated in all observation fields is defined as the ferrite area ratio (%). In addition, the ferrite area ratio is set to an integer obtained by rounding off the first decimal place. In addition, the austenite area ratio (%) is calculated using the following formula.
[0261] Austenite area ratio = 100 - ferrite area ratio
[0262] [For (Feature 2) Ferrite average thickness TF, sample standard deviation ΔTF, austenite average thickness TA]
[0263] The length direction of the duplex stainless steel material is defined as the L direction, and the thickness direction of the duplex stainless steel material is defined as the T direction. In the cross section of the duplex stainless steel material including the L direction and the T direction, three rectangular areas are determined at intervals of 100 mm in the L direction. Each determined area is set as a rectangle of 200 μm in the L direction and 200 μm in the T direction. In each rectangular area, five line segments are defined as line segments LS, which are line segments extending in the T direction and are arranged at equal intervals in the L direction of the rectangular area, dividing the rectangular area into six equal parts in the L direction. In this case, the duplex stainless steel material of the present embodiment satisfies the following (1) to (3).
[0264] (1) The average thickness TF of each ferrite in the three rectangular regions overlapping the 15 line segments LS is 2.50 to 4.50 μm.
[0265] (2) The sample standard deviation ΔTF of the thickness of ferrite is 0.50 μm or less.
[0266] (3) The average thickness TA of each austenite overlapping the 15 line segments LS is 2.50 to 4.50 μm.
[0267] Feature 2 will be discussed in detail below.
[0268] [Method for measuring the average ferrite thickness TF, the sample standard deviation of the ferrite thickness ΔTF, and the average austenite thickness TA]
[0269] The average ferrite thickness TF, the sample standard deviation ΔTF of the ferrite thickness, and the average austenite thickness TA can be measured by the following method.
[0270] A test piece was collected from the middle portion of the thickness of the duplex stainless steel material, and the test piece included a longitudinal section including the L direction and the T direction on the surface.
[0271] Figure 3 This is a longitudinal cross-sectional view of the sampling position of the test piece for explaining the case where the duplex stainless steel material is a steel pipe. Figure 3 The dashed line C1 in the figure is the pipe axis. The dashed line L1 is a dashed line passing through the center of the wall thickness of the steel pipe. Figure 3 In the case where the duplex stainless steel material is a steel pipe, in a cross section (longitudinal section) including the L direction and the T direction, three rectangular areas TP are determined at a pitch of P = 100 mm in the center of the wall thickness and in the L direction. In addition, three test pieces including each rectangular area TP on the surface are collected. The rectangular area TP is set to 200 μm in the L direction and 200 μm in the T direction.
[0272] When the duplex stainless steel material is a steel plate, similarly, in a longitudinal section including the L direction (rolling direction) and the T direction (plate thickness direction), three rectangular regions TP are determined at 100 mm intervals in the center of the plate thickness and in the L direction. And three test pieces including each rectangular region TP on the surface are collected.
[0273] When the duplex stainless steel material is a steel bar, similarly, in a longitudinal section including the L direction (center axis direction) and the T direction (radial direction), three rectangular areas TP are determined at a 100 mm pitch in the radial center (that is, the center axis) and in the L direction. And three test pieces including each rectangular area TP on the surface are collected.
[0274] The surface including the rectangular region TP among the surfaces of the test piece is defined as the observation surface. In addition, the size of the test piece is not particularly limited, and any size including the rectangular region TP may be sufficient.
[0275] The observation surface of the test piece was mirror-polished. The mirror-polished observation surface was electrolytically etched in a 30% sodium hydroxide etching solution to visualize the structure. The rectangular area TP on the observation surface was observed at 500 times using an optical microscope.
[0276] Figure 4 is a schematic diagram of the rectangular area TP. Figure 4 The rectangular region is a rectangle with a length of 200 μm in the L direction and a length of 200 μm in the T direction. In the rectangular region TP, five line segments LS are arranged at equal intervals in the L direction and divide the rectangular region TP into six equal parts in the L direction. At this time, each line segment LS overlaps with the ferrite F and austenite A in the rectangular region TP.
[0277] Figure 5 yes Figure 4 An enlarged view of the area overlapping the line segment LS1 in the rectangular area TP in FIG. Figure 5 , line segment LS1 overlaps with ferrite F1 to F5 and austenite A1 to A5. The length of ferrite F1 overlapping with line segment LS1 is set as the thickness TF1 of ferrite F1, and the thickness TF1 is calculated. Similarly, the thicknesses TF2 to TF5 of ferrite F2 to F5 overlapping with line segment LS1 are calculated. Similarly, the thicknesses TA1 to TA6 of austenite A1 to A6 overlapping with line segment LS1 are calculated.
[0278] for Figure 4 Similarly, for the other four line segments LS, the length of the overlap between the ferrite F and the line segment LS is set to the thickness of the ferrite F. The length of the overlap between the austenite A and the line segment LS is set to the thickness of the austenite A.
[0279] The above method is used to obtain the thickness TF of each ferrite F and the thickness TA of each austenite A in the three rectangular areas TP overlapping with the 15 line segments. The arithmetic mean of the thickness of all ferrites obtained is set as the average thickness TF (μm) of ferrite. The sample standard deviation ΔTF (μm) is obtained based on the thickness of all ferrites obtained and the average thickness TF of ferrite.
[0280] In addition, the arithmetic mean of the obtained thicknesses of all austenites is defined as the average thickness TA (μm) of austenite.
[0281] [Regarding feature 2 (1) to (3)]
[0282] The average thickness TF of ferrite, the sample standard deviation ΔTF of the thickness of ferrite, and the average thickness TA of austenite obtained by the above-mentioned measurement satisfy the following (1) to (3).
[0283] (1) The average thickness TF of each ferrite in the three rectangular regions overlapping the 15 line segments LS is 2.50 to 4.50 μm.
[0284] (2) The sample standard deviation ΔTF of the thickness of ferrite is 0.50 μm or less.
[0285] (3) The average thickness TA of each austenite overlapping the 15 line segments LS is 2.50 to 4.50 μm.
[0286] If the average thickness TF of ferrite is greater than 4.50 μm, the thickness of ferrite is too large. In this case, when the duplex stainless steel is welded to form a welded joint, Cr nitrides and secondary austenite are easily generated in the HAZ. Therefore, the intergranular corrosion resistance in the case of a welded joint is reduced. If the average thickness TF of ferrite is less than 4.50 μm, the thickness of ferrite is sufficiently small. Therefore, sufficient intergranular corrosion resistance can also be obtained in the case of a welded joint.
[0287] The lower limit of the average thickness TF of ferrite is not particularly limited. The lower limit of the average thickness TF of ferrite is, for example, 2.50 μm.
[0288] The upper limit of the average thickness TF of ferrite is preferably 4.45 μm, more preferably 4.40 μm, and further preferably 4.35 μm.
[0289] The lower limit of the average thickness TF of ferrite is preferably 2.55 μm, more preferably 2.60 μm.
[0290] Furthermore, when the average thickness TF of ferrite is 2.50 to 4.50 μm, the average thickness TA of austenite is 2.50 to 4.50 μm.
[0291] The upper limit of the average thickness TA of austenite is preferably 4.45 μm, more preferably 4.40 μm, and further preferably 4.35 μm.
[0292] The lower limit of the average thickness TA of austenite is preferably 2.55 μm, more preferably 2.60 μm.
[0293] In addition, regarding ferrite, the sample standard deviation ΔTF of the thickness of ferrite is 0.50 μm or less. As described above, even if the average thickness TF of ferrite is sufficiently small, if the fluctuation of the thickness of ferrite in the L direction of the duplex stainless steel material increases, there is a portion with a locally large thickness in the ferrite extending along the L direction. In this case, Cr nitrides and secondary austenite are easily generated in the portion with a locally large thickness during welding. Therefore, in the case of a welded joint, the intergranular corrosion resistance is reduced.
[0294] If the sample standard deviation ΔTF of the ferrite thickness is 0.50 μm or less, the fluctuation of the ferrite thickness in the L direction is sufficiently small. Therefore, sufficient intergranular corrosion resistance can be obtained in the case of a welded joint on the premise of satisfying the above (1) and (3).
[0295] The upper limit of the sample standard deviation ΔTF is preferably 0.48 μm, more preferably 0.45 μm, and further preferably 0.43 μm.
[0296] [Effects of the duplex stainless steel material of this embodiment]
[0297] The duplex stainless steel material of the present embodiment satisfies the feature 1 and the feature 2. Therefore, in the duplex stainless steel material of the present embodiment, even in the case of a welded joint, excellent intergranular corrosion resistance can be obtained.
[0298] [About intergranular corrosion resistance]
[0299] In the duplex stainless steel material of the present embodiment, sufficient intergranular corrosion resistance can be obtained in the case of a welded joint, which means that the corrosion rate obtained by performing a nitric acid corrosion test of ASTM A262 Practice C on a welded joint using the duplex stainless steel material of the present embodiment as a base material is 0.100 g / m 2 / h or less.
[0300] [Evaluation method for intergranular corrosion resistance]
[0301] The intergranular corrosion resistance of the duplex stainless steel material according to the present embodiment can be evaluated by the following method.
[0302] First, a welded joint of a duplex stainless steel material is manufactured. Specifically, a pair of duplex stainless steel materials are prepared. A groove is formed at the end of the prepared duplex stainless steel material. The shape of the groove is set to a U groove with a groove angle of 20°. The grooves of a pair of duplex stainless steel materials are butted and welded. A welding material whose chemical composition satisfies the above-mentioned feature 1 is prepared. A pair of duplex stainless steel materials are welded using automatic gas tungsten arc welding (GTAW) using the prepared welding material. The heat input at this time is set to 0.5 to 4.00 kJ / mm. A test piece including a welded portion in the center is collected from the welded joint of the manufactured duplex stainless steel material. Specifically, a test piece extending in a direction perpendicular to the extension direction of the welded portion of the welded joint of the duplex stainless steel material is collected. The size of the test piece is set to 2 mm in thickness × 10 mm in width × 40 mm in length. The test piece is collected in a manner such that the weld metal is arranged in the central position in the longitudinal direction of the test piece. In addition, the test piece is collected in a manner such that the maximum value of the width of the weld metal in the longitudinal direction of the test piece is less than 25 mm.
[0303] The nitric acid corrosion test of ASTM A262 Practice C is carried out using the collected test pieces. Specifically, an aqueous solution having a nitric acid concentration of 65% by mass, i.e., a test solution, is prepared. The test piece is immersed in the boiling test solution for 48 hours (the first immersion test). After the test, a new test solution is prepared, and the immersion test is carried out in the same manner as the first time. Specifically, the test piece is taken out from the test solution used for the first immersion test, and the test piece is immersed in the test solution used for the second immersion test for 48 hours. Such an immersion test is repeated 10 times (the first to the tenth time) or more.
[0304] Before and after each immersion test (1st to 10th time), the mass of the test piece was measured and the difference (mass loss) was calculated. Based on the mass loss, the mass loss per unit area and per unit time of the test piece was calculated in each immersion test (hereinafter referred to as unit mass loss, unit is g / m 2 The arithmetic mean of the unit mass reductions obtained 10 times (the 1st to the 10th time) is defined as the corrosion rate (g / m 2 / h).
[0305] If the corrosion rate obtained is 0.100 g / m 2 / h or less, it is judged that sufficient intergranular corrosion resistance is obtained in the case of a welded joint.
[0306] [Shape of the Duplex Stainless Steel Material of the Present Embodiment]
[0307] As described above, the duplex stainless steel material of the present embodiment may be a steel pipe, a steel plate, or a steel bar. Preferably, the duplex stainless steel material of the present embodiment is a steel pipe. More preferably, the duplex stainless steel material of the present embodiment is a seamless steel pipe.
[0308] [Application of the duplex stainless steel material of this embodiment]
[0309] The duplex stainless steel material of this embodiment can be widely used in applications requiring intergranular corrosion resistance. In particular, the duplex stainless steel material of this embodiment is suitable for steel materials for urea production plants. However, the application of the duplex stainless steel material of this embodiment is not limited to the above range.
[0310] [Manufacturing method of duplex stainless steel]
[0311] An example of a method for manufacturing a duplex stainless steel material according to the present embodiment will be described. The method for manufacturing a duplex stainless steel material described later is an example for manufacturing the duplex stainless steel material according to the present embodiment. Therefore, the duplex stainless steel material having the above-mentioned structure may also be manufactured by other manufacturing methods other than the manufacturing method described later. However, the manufacturing method described later is a preferred example of the method for manufacturing a duplex stainless steel material according to the present embodiment.
[0312] An example of a method for producing a duplex stainless steel material according to the present embodiment includes the following steps.
[0313] (Process 1) Raw material preparation process
[0314] (Process 2) Hot working process
[0315] (Process 3) Cold working process
[0316] (Step 4) Solution Treatment Step
[0317] The main production conditions in the above-mentioned steps 1 to 4 are as follows.
[0318] (Condition 1) Reduction of area during hot working process R1: 60% or more
[0319] (Condition 2) Cooling rate after hot working CR1: 50°C / sec or more (water cooling)
[0320] (Condition 3) Reduction of area R2 during cold working: 60% or more
[0321] (Condition 4) FA defined by formula (A): 150 to 500
[0322] FA=R1 / 100×K CR ×R2 / 100×T1×(t1 / 60) 0.5 (A)
[0323] Here, T1 in formula (A) is the solution temperature (°C) in the solution treatment process, and t1 is the holding time (minutes) at the solution temperature T1. CR When the cooling rate CR1 just after hot working is 50°C / sec or more (water cooling), substitute "1.2", and when the cooling rate CR1 just after hot working is less than 50°C / sec (natural cooling), substitute "0.8".
[0324] Hereinafter, each step will be described.
[0325] [(Process 1) Raw material preparation process]
[0326] In the raw material preparation process, raw materials having a chemical composition satisfying feature 1 are prepared. The raw material may be a steel ingot, or may be a slab, a bloom, or a billet. When manufacturing the raw material, the raw material is manufactured using the following method. Molten steel having a chemical composition satisfying feature 1 is manufactured. The manufactured molten steel is used to manufacture an ingot by an ingot casting method. The manufactured molten steel may also be used to manufacture a slab, a bloom, or a billet (cylindrical raw material) by a continuous casting method. The manufactured ingot, slab, or billet may also be subjected to hot working to manufacture a billet. For example, a cylindrical billet may be manufactured by hot forging a steel ingot, and the billet may be used as a raw material (cylindrical raw material). In this case, the temperature of the raw material immediately before hot forging is not particularly limited, and is, for example, 1000 to 1300°C. The cooling method of the raw material after hot forging is not particularly limited.
[0327] [(Process 2) Hot working process]
[0328] In the hot working step, the raw material prepared in the raw material preparation step is hot worked to produce an intermediate steel material. The intermediate steel material may be a steel pipe, a steel plate, or a steel bar.
[0329] When the intermediate product is a steel pipe, the following processing is performed in the hot working process. First, a cylindrical raw material is prepared. A through hole is formed along the central axis of the cylindrical raw material by machining. The cylindrical raw material with the through hole is subjected to hot extrusion represented by the glass lubricant high-speed extrusion method to manufacture the intermediate product (seamless steel pipe). The temperature of the raw material immediately before hot extrusion is not particularly limited. The heating temperature of the raw material immediately before hot extrusion is, for example, 1000 to 1300°C.
[0330] When the intermediate product is a steel plate, the hot working step uses, for example, one or more rolling mills equipped with a pair of work rolls. The rolling mill hot-rolls a raw material such as a slab to produce a steel plate. The heating temperature of the raw material during hot rolling is, for example, 1000 to 1300°C.
[0331] When the intermediate product is a steel bar, the hot working process includes, for example, a rough rolling process and a finishing rolling process. In the rough rolling process, the raw material is hot worked to produce a steel billet. The rough rolling process uses, for example, a rough rolling mill. The rough rolling mill is used to perform rough rolling on a large steel billet to produce a steel billet. In the case where a continuous rolling mill is arranged downstream of the rough rolling mill, the continuous rolling mill can also be used to perform hot rolling on the steel billet after the rough rolling to further produce a steel billet of smaller size. In the continuous rolling mill, for example, a horizontal frame having a pair of horizontal rollers and a vertical frame having a pair of vertical rollers are alternately arranged in a row. The temperature of the raw material immediately before the rough rolling process is not particularly limited, and is, for example, 1000 to 1300°C. In the finishing rolling process, the steel billet is first heated. The heated steel billet is hot rolled using a continuous rolling mill to produce a steel bar. The heating temperature in the hot furnace in the finishing rolling process is not particularly limited, and is, for example, 1000 to 1200°C.
[0332] The intermediate steel material immediately after hot working is quenched. Specifically, the intermediate steel material immediately after hot working is water-cooled. Due to water cooling, the cooling rate CR1 of the intermediate steel material becomes 50°C / second or more. The intermediate steel material is cooled to room temperature by water cooling. By water cooling the intermediate steel material, the strain accumulated in the hot working process is suppressed from being released.
[0333] Furthermore, the intermediate steel material after water cooling is not subjected to heat treatment such as annealing, but is subjected to a cold working step in the next step, thereby suppressing the release of strain accumulated in the hot working step.
[0334] [(Process 3) Cold working process]
[0335] In the cold working process, the intermediate steel material manufactured by the hot working process is cold worked. When the intermediate steel material is a steel pipe or a steel bar, the cold working is cold drawing or pilger cold rolling. When the intermediate steel material is a steel plate, the cold working is, for example, cold rolling. By implementing the cold working process, strain is further accumulated in the intermediate steel material before the solution treatment. As a result, during the solution treatment, fine austenite is precipitated with the accumulated strain as the core, and as a result, ferrite with less thickness fluctuation in the L direction can be obtained.
[0336] In addition, descaling treatment may be performed before cold working is performed on the intermediate steel material after the hot working step. Descaling treatment may not be performed. When descaling treatment is performed, the descaling treatment is, for example, shot peening and / or pickling.
[0337] [(Step 4) Solution treatment step]
[0338] In the solution treatment process, the intermediate steel material after the cold working process is subjected to solution treatment. In the solution treatment, the precipitates are dissolved. Moreover, in the present embodiment, in the solution treatment, due to the strain accumulated in the intermediate steel material in the hot working process and the cold working process, ferrite with less fluctuation in thickness in the L direction is formed. The solution temperature T1 in the solution treatment is 1000 to 1200°C. The holding time t1 at the solution temperature T1 is 1.00 to 50.00 minutes.
[0339] [For conditions 1 to 4]
[0340] In the above-mentioned manufacturing process, each process is performed so as to satisfy the following conditions.
[0341] (Condition 1) Reduction of area during hot working process R1: 60% or more
[0342] (Condition 2) Cooling rate after hot working CR1: 50°C / sec or more (water cooling)
[0343] (Condition 3) Reduction of area R2 during cold working: 60% or more
[0344] (Condition 4) FA defined by formula (A): 150 to 500
[0345] FA=R1 / 100×K CR ×R2 / 100×T1×(t1 / 60) 0.5 (A)
[0346] Here, T1 in formula (A) is the solution temperature (°C) in the solution treatment process, and t1 is the holding time (minutes) at the solution temperature T1. CR When the cooling rate CR1 just after hot working is 50°C / sec or more (water cooling), substitute "1.2", and when the cooling rate CR1 just after hot working is less than 50°C / sec (natural cooling), substitute "0.8".
[0347] Each condition is described below.
[0348] [For condition 1]
[0349] The reduction of area R1 (%) in the hot working step is defined by the following formula.
[0350] Sectional reduction ratio R1 = (1-the cross-sectional area perpendicular to the length direction of the intermediate steel after hot working / the cross-sectional area perpendicular to the length direction of the raw material) × 100
[0351] If the reduction of area R1 is less than 60%, the strain accumulated in the intermediate steel material is insufficient. Therefore, the duplex stainless steel material after production cannot satisfy the characteristic 2. Therefore, the reduction of area R1 is 60% or more.
[0352] [For condition 2]
[0353] The cooling rate CR1 of the intermediate steel material just after hot working is set to 50°C / sec or more. This cooling rate is achieved by water cooling. When the intermediate steel material is air cooled, the cooling rate CR1 is slower than 50°C / sec. If the intermediate steel material just after hot working is not water cooled but air cooled, the strain accumulated in the intermediate steel material due to hot working will be released during the cooling process. Therefore, the amount of strain used to make the metallographic structure of feature 2 appear in the solution treatment is insufficient. Therefore, the cooling rate CR1 is set to 50°C / sec or more.
[0354] [For condition 3]
[0355] The reduction of area R2 (%) in the cold working process is defined by the following formula.
[0356] Sectional reduction ratio R2 = (1-the cross-sectional area perpendicular to the length direction of the intermediate steel after cold working / the cross-sectional area perpendicular to the length direction of the intermediate steel before cold working) × 100
[0357] If the reduction of area R2 is less than 60%, the strain accumulated in the intermediate steel material is insufficient. Therefore, the duplex stainless steel material after production cannot satisfy the characteristic 2. Therefore, the reduction of area R2 is 60% or more.
[0358] [For condition 4]
[0359] In the above-mentioned production process, FA defined by formula (A) is 150-500.
[0360] FA=R1 / 100×K CR ×R2 / 100×T1×(t1 / 60) 0.5 (A)
[0361] Here, T1 in formula (A) is the solution temperature (°C) in the solution treatment process, and t1 is the holding time (minutes) at the solution temperature T1. CR When the cooling rate CR1 just after hot working is 50°C / sec or more (water cooling), substitute "1.2", and when the cooling rate CR1 just after hot working is less than 50°C / sec (natural cooling), substitute "0.8".
[0362] FA is a manufacturing condition for making the metallographic structure of duplex stainless steel satisfy Feature 2. CR×R2 / 100” is a factor related to the amount of strain accumulation, and “T1×(t1 / 60) 0.5 " is a factor for making the precipitation of austenite appear during solution treatment. If FA is 150-500, sufficient strain is accumulated in the intermediate steel before solution treatment, and the conditions in solution treatment are also appropriate. Therefore, the metallographic structure of the duplex stainless steel after manufacture satisfies feature 2.
[0363] The duplex stainless steel material satisfying the first and second characteristics can be manufactured by the above-described manufacturing process.
[0364] The effects of the duplex stainless steel material of the present embodiment will be described in more detail below using examples. The conditions in the following examples are one condition example adopted to confirm the feasibility and effects of the duplex stainless steel material of the present embodiment. Therefore, the duplex stainless steel material of the present embodiment is not limited to this one condition example.
[0365] Example
[0366] Duplex stainless steel pipes (seamless steel pipes) having the chemical compositions shown in Table 1-1 and Table 1-2 were manufactured.
[0367] [Table 1-1]
[0368] Table 1-1
[0369]
[0370] [Table 1-2]
[0371] Table 1-2
[0372]
[0373] The "-" in Table 1-2 means that the corresponding element content is 0% in the case of the significant figures (the minimum number of digits) specified in the implementation method. In other words, it means that in the corresponding element content, in the above-mentioned implementation method, the zero number is rounded to the specified significant figures (the minimum number of digits) and is 0%. For example, it means that the Cu content of test number 1 is "0" when rounded to the third decimal place. The remainder other than the elements recorded in Tables 1-1 and 1-2 is Fe and impurities.
[0374] Specifically, first, in the raw material preparation process, a large steel billet having the chemical composition shown in Table 1-1 and Table 1-2 was manufactured. The large steel billet was hot forged to manufacture a cylindrical raw material (round steel billet). The heating temperature of the large steel billet during hot forging was 1100 to 1250° C. The round steel billet after hot forging was naturally cooled to room temperature.
[0375] In the hot working process, the round billet is hot extruded to produce a steel pipe (seamless steel pipe) as an intermediate steel material. The heating temperature of the round billet during hot working is 1100 to 1200° C. The cross-sectional reduction ratio R1 (%) during hot working is as shown in Table 2.
[0376] [Table 2]
[0377] Table 2
[0378]
[0379] The intermediate steel material immediately after hot working is cooled to room temperature. The cooling rate CR1 (°C / sec) is as shown in Table 2. The intermediate steel material after cooling is not subjected to annealing treatment, etc., but is subjected to cold working. Specifically, the intermediate steel material is cold worked using a pilger mill. The cross-sectional reduction rate R2 (%) during cold working is as shown in Table 2.
[0380] The intermediate steel material after the cold working process was subjected to a solution treatment process. In the solution treatment process, the solution treatment temperature T1 was set to 1000 to 1200°C, and the holding time t1 at the solution treatment temperature T1 was set to 1.00 to 50.00 minutes. In addition, the FA value of each test number is as shown in Table 2.
[0381] The duplex stainless steel material (seamless steel pipe) was manufactured through the above manufacturing steps.
[0382] [Evaluation test]
[0383] The following evaluation tests were performed on the duplex stainless steel materials of each test number produced.
[0384] (Test 1) Ferrite area ratio measurement test
[0385] (Test 2) Test for measuring the average ferrite thickness TF, sample standard deviation ΔTF, and average austenite thickness TA
[0386] (Test 3) Intergranular corrosion resistance evaluation test for welded joints
[0387] Hereinafter, Tests 1 to 3 will be described.
[0388] [(Test 1) Ferrite area ratio measurement test]
[0389] The ferrite area ratio of the duplex stainless steel material of each test number was determined based on the method described in the above-mentioned [Method for measuring the ferrite area ratio]. As a result, in all test numbers, the metallographic structure was composed of ferrite and austenite, and the ferrite area ratio was 35 to 55%.
[0390] [(Test 2) Test for measuring the average thickness TF of ferrite, the standard deviation ΔTF of samples, and the average thickness TA of austenite]
[0391] Based on the above-mentioned [Method for measuring the average ferrite thickness TF, the sample standard deviation ΔTF of the ferrite thickness, and the average austenite thickness TA], the average ferrite thickness TF, the sample standard deviation ΔTF, and the average austenite thickness TA in the duplex stainless steel material of each test number were obtained. The obtained results are shown in Table 2.
[0392] [(Test 3) Intergranular corrosion resistance evaluation test in case of welded joint]
[0393] The welded joints of duplex stainless steel materials of each test number were manufactured by the method described in the above-mentioned [Method for evaluating intergranular corrosion resistance]. In addition, the nitric acid corrosion test of ASTM A262 Practice C was carried out using the test pieces collected from the welded joints by the method described in the above-mentioned [Method for evaluating intergranular corrosion resistance], and the corrosion rate (g / m 2 The obtained corrosion rates are shown in Table 2.
[0394] [Evaluation results]
[0395] Referring to Table 1-1, Table 1-2, and Table 2, the duplex stainless steel materials of Test Nos. 1 to 13 satisfy Characteristics 1 and 2. Therefore, in the duplex stainless steel materials of these Test Nos., the corrosion rate in the case of the welded joint is 0.100 g / m 2 / h or less, sufficient intergranular corrosion resistance is obtained.
[0396] On the other hand, in Test No. 14, the reduction of area R1 in the hot working process was less than 60%. Therefore, the duplex stainless steel material did not satisfy Feature 2. As a result, the corrosion rate in the case of the welded joint was greater than 0.100 g / m 2 / h, sufficient intergranular corrosion resistance cannot be obtained.
[0397] In test number 15, the cooling rate CR1 after hot working is less than 50°C / sec. Therefore, the FA value is less than 150. Therefore, the duplex stainless steel material does not satisfy feature 2. As a result, the corrosion rate in the case of the welded joint is greater than 0.100 g / m 2 / h, sufficient intergranular corrosion resistance cannot be obtained.
[0398] In test number 16, the reduction of area R2 in the cold working process was less than 60%. Therefore, the duplex stainless steel material did not satisfy characteristic 2. As a result, the corrosion rate in the case of the welded joint was greater than 0.100 g / m 2 / h, sufficient intergranular corrosion resistance cannot be obtained.
[0399] In test numbers 17 to 19, although the reduction of area R1, cooling rate CR1, and reduction of area R2 are appropriate, the FA value is less than 150. Therefore, the duplex stainless steel material does not satisfy feature 2. As a result, the corrosion rate in the case of the welded joint is greater than 0.100 g / m 2 / h, sufficient intergranular corrosion resistance cannot be obtained.
[0400] In test numbers 20 and 21, although the reduction of area R1, cooling rate CR1, and reduction of area R2 are appropriate, the FA value is greater than 500. Therefore, the duplex stainless steel material does not satisfy feature 2. As a result, the corrosion rate in the case of the welded joint is greater than 0.100 g / m 2 / h, sufficient intergranular corrosion resistance cannot be obtained.
[0401] The embodiments of the present disclosure have been described above. However, the above embodiments are merely examples for implementing the present disclosure. Therefore, the present disclosure is not limited to the above embodiments, and the above embodiments can be appropriately modified and implemented within the scope of the present disclosure.
Claims
1. A duplex stainless steel material, the chemical composition of which is C: 0.030% or less, Si: 0.50% or less, Mn: 2.00% or less, P: 0.040% or less, S: 0.0010% or less, Cr:26.0~28.0%、 Ni: 6.0-10.0%, Mo: 0.20~1.70%, W: more than 2.00% and less than 3.00%, N: more than 0.30% and less than 0.40%, O: 0.020% or less, Al: 0.050% or less, Cu: 0-0.30%, Co: 0-1.0%, Ti: 0~0.300%, Nb: 0~0.300%, Ca: 0~0.010% Mg: 0~0.010%, B: 0 to 0.010%, and The balance is Fe and impurities. The length direction of the duplex stainless steel material is defined as the L direction, and the thickness direction of the duplex stainless steel material is defined as the T direction. In a cross section of the duplex stainless steel material including the L direction and the T direction, three rectangular regions are defined at intervals of 100 mm in the L direction, and each defined region is a rectangle of 200 μm in the L direction and 200 μm in the T direction. In each of the rectangular areas, When five line segments are defined as line segments LS, the five line segments are line segments extending in the T direction, and are arranged at equal intervals in the L direction of the rectangular area, dividing the rectangular area into six equal parts in the L direction. The average thickness TF of each ferrite in the three rectangular regions overlapping the 15 line segments LS is 2.50 to 4.50 μm, and the sample standard deviation ΔTF of the thickness of the ferrite is 0.50 μm or less. The average thickness TA of each austenite overlapping the 15 line segments LS is 2.50 to 4.50 μm.
2. The duplex stainless steel material according to claim 1, wherein: The chemical composition contains a Cu: 0.01-0.30%, Co: 0.1-1.0%, Ti: 0.001~0.300%, Nb: 0.001~0.300%, Ca: 0.001~0.010%, Mg: 0.001-0.010%, and B: One or more elements selected from the group consisting of 0.001 to 0.010%.
3. The duplex stainless steel material according to claim 1 or 2, wherein: The duplex stainless steel material is a seamless steel pipe.
Citation Information
Patent Citations
Two-phase stainless steel for urea-producing plant, welding material, urea-producing plant and equipment therefor
JP2003301241A
Duplex stainless steel for urea production plant, and urea production plant
JP2011127186A
Cited By
Duplex stainless steel as well as preparation method and application thereof
CN120967241A